Deus Migrator dan Komunitas Diaspora:: Sebuah Tinjauan Terhadap Misiologi - Jonathan Wijaya (Sekolah Tinggi Teologi Bandung, 2023)
Nowadays, migration is unavoidable. According to statistics, the number of Christian migrants is 106 million, or 49% of the world's 214 million international migrants. Then, Muslims make up the second largest share of people who have migrated across borders at nearly 60 million, or 27%. Meanwhile, Hindus (almost 11 million) contributed 5% and Buddhists (about 7 million) contributed 3% (pewresearch.org). How can a Christian interpret it? And how should Christians respond? Through this writing, the author argues that God is the Great Migrator, called Deus Migrator, who calls His people to become God's representatives in the world in the form of a diaspora community that carries out the Great Commission from God. To achieve this, the author firstly explains the biblical fundamental for Deus Migrator from Peter C. Phan, both in the OT and NT. Then, the author describes the diaspora community of Enoch Wan. Lastly, the writer will provide an analysis and a conclusion that says missions are not always going somewhere, but by accepting migrants in our respective places; mission relates not only to the world to come, but also to the world today; and migrants are not an object to be forced to become Christians.